1986
DOI: 10.1042/bj2390473
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 17-hydroxyprogesterone by a Bacillus species

Abstract: Fermentation of 17-hydroxyprogesterone with a Bacillus species (IICB-301) in a modified nutrient medium under aerobic conditions yielded androst-4-ene-3,17-dione and 15 alpha,17-dihydroxypregn-4-ene-3,20-dione in addition to a new pregnane analogue, 6 beta,17,20 alpha-trihydroxypregn-4-ene-3-one. Each microbial metabolite was characterized by the application of various spectroscopic techniques. The availability of the new metabolite, 6 beta,17,20 alpha-trihydroxypregn-4-ene-3-one, enabled complete elucidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However their transformation by thermophilic bacteria has not been fully explored and the transformation of hydroxyprogesterone derivatives by thermophiles has been recently reported (Al-Awadi et al 2006). Even though microbial assisted hydroxylation products are commonly reported, steroid side chain cleavage is rare in Bacillus species (Mahato & Banerjee 1986). Cleavage of a steroid side chain at C17 is considered an important step in the synthesis of C 19 steroid hormones (Smith 1984;Mahato & Banerjee 1985).…”
Section: Introductionmentioning
confidence: 99%
“…However their transformation by thermophilic bacteria has not been fully explored and the transformation of hydroxyprogesterone derivatives by thermophiles has been recently reported (Al-Awadi et al 2006). Even though microbial assisted hydroxylation products are commonly reported, steroid side chain cleavage is rare in Bacillus species (Mahato & Banerjee 1986). Cleavage of a steroid side chain at C17 is considered an important step in the synthesis of C 19 steroid hormones (Smith 1984;Mahato & Banerjee 1985).…”
Section: Introductionmentioning
confidence: 99%
“…However, steroids with hydroxyl group at 17fl-position as in testosterone ( 21) is readily transformed to its 14~t-hydroxy derivative (Krishnan et al 1991). Earlier, it has been demonstrated that incubation of 170t-hydroxyprogesterone (7) with a Bacillus species results in the formation of a side-chain cleaved product (Mahato and Banerjee 1986). It appears that M. piriformis is not capable of cleaving the C17 side-chain in a C2x steroid.…”
Section: Transformations Of 17ct-hydroxypro#esterone (Z)mentioning
confidence: 99%